A Learning Strategies for the Digital Age in Bimbel Little Josua (Non-Formal Education) in Pagarbatu, North Tapanuli: Learning Strategies for the Digital Age - Tambunan, Abai; Bryan King Hutagalung; Alki Firton Tambunan; Emmi Silvia Herlina (PRODI PKAUD, IAKN TARUTUNG, 2023)
Abstract Technology is a form of progress of the times that requires every human being to follow it so that humans can survive and facilitate human activities, we also feel these demands in the learning process both formal and non-formal learning, in this case, qualitative research was carried out with a case study approach to tutoring for Little Josua in Pagarbatu Village, Sipaholon District, North Tapanuli Regency, North Sumatra, the data were obtained by triangulation techniques, and determining informants by snow ball sampling technique, and making the knowledge of the researchers a key instrument. From this study it was found that non-formal education learning is more controlled, effective and efficient because control efforts use strategies that are integrated with digital utilization.